A Case of Endometrial Carcinosarcoma Containing Sertoliform Endometrioid Carcinoma Component. (21st September 2021) - Munakata, Satoru; Kushibiki, Hanae; Akimoto, Taishi; Yamashita, Tsuyoshi; Shimoyama, Norihiko
Abstract : Carcinosarcomas (CSs) of the endometrium have admixture of malignant epithelial and mesenchymal components. The carcinomatous component exhibit endometrioid, serous, or clear cell differentiation, or are undifferentiated. CSs are considered homologous or heterologous according to the type of sarcomatous component. Sertoliform endometrioid carcinomas (SECs) of the endometrium which comprise a rare subtype of endometrial cancer, typically occur in the ovary. SECs as a carcinomatous component of CS of the endometrium have not been reported. Here, we report an endometrial carcinosarcoma that contains an SEC component. An 88-year-old female presented to a clinic with atypical genital bleeding. She was referred to our hospital and underwent total hysterectomy, bilateral adnexectomy and partial omentectomy due to endometrial carcinoma. Gross examination revealed a polypoid mass in the uterine cavity with massive myometrial invasion. Histologically, the tumor was a high-grade endometrioid carcinoma. In addition to an ordinary conventional endometrioid carcinoma, approximately 30% of the area exhibited sex cord-like pattern and contained small hollow tubules, anastomosing cords and trabeculae, and tightly packed nests. Immunohistochemically, the SEC component showed diffuse p53 staining. Sex cord-like area, especially the solid area, showed positive staining for EMA, vimentin, α -inhibin, CD99, calretinin, p53, CD56, synaptophysin, and chromogranin A, which is a staining pattern similar to that previously reported SEC of the endometrium. Diminished membranous and positive cytoplasmic staining for β -catenin was observed. This is the first case report of an endometrial carcinosarcoma containing an SEC component. SECs of the endometrium might exhibit sex cord-like differentiation in contrast to SECs of the ovary, which do not exhibit sex cord differentiation.